Lymphocyte Immune Response and T Cell Differentiation in Fontan Patients with protein-losing enteropathy - Moosmann, Julia; Toka, Okan; Lukassen, Sören; Ekici, Arif B.; Mackensen, Andreas; Völkl, Simon; Dittrich, Sven (The Thoracic and Cardiovascular Surgeon, 2021)
Background Protein-losing enteropathy (PLE) is a severe complication of the Fontan circulation. There is increasing discussion about whether lymphatic dysregulation is involved as pathomechanism of PLE. This investigation focuses on the interplay between alteration of lymphatic cells and immunologic pathway alterations.Methods Micro-ribonucleic acid (miRNA) expression profiling was performed in 49 patients (n = 10 Fontan patients with PLE, n = 30 Fontan patients without PLE, and n = 9 patients with dextro-transposition of the great arteries (dTGA). miRNA pathway analysis was performed to identify significantly enriched pathways. To determine lymphocyte populations and subtypes multiparameter flow cytometry was used.Results miRNAs pathway analysis of Fontan patients with PLE revealed 20 significantly changed networks of which four of the ten largest were associated with immunologic processes. This finding is supported by significant T cell deficiency with decreased CD4+ count (p = 0.0002), altered CD4 +/CD8+ ratio, and significantly modified CD4+ (p < 0.0001) and CD8+ (p = 0.0002) T cell differentiation toward effector and terminal differentiated T cells in Fontan patients with PLE. Analyses of CD4+ T cell subsets demonstrated significantly increased frequencies of CD4+ CD25+ CD127– regulatory T cells (Treg) in Fontan patients with PLE (p = 0.0011).Conclusion PLE in Fontan patients is associated with severe lymphopenia, T cell deficiency, significant alterations of T cell differentiation, and increased Treg frequency reflecting an immune status of chronic inflammation and shortened protection against pathogens and autoimmunity. These cellular alterations seemed to be dysregulated by several miRNA controlled immunological pathways.
Keywords: congenital heart disease (CHD); inflammation; systemic; genetics; genomics